LOAD2: A late‐onset Alzheimer's disease mouse model expressing APOEε4, Trem2*R47H, and humanized amyloid‐beta. (December 2021) - Kotredes, Kevin P; Oblak, Adrian L; Preuss, Christoph; Pandey, Ravi S; Territo, Paul R; Rizzo, Stacey J Sukoff; Carter, Gregory W; Sasner, Michael; Howell, Gareth R; Lamb, Bruce T.
Abstract: Background: Alzheimer's disease (AD) is the most common form of dementia without an approved therapy. Current animal models do not fully recapitulate late‐onset AD (LOAD), thus are not ideal for therapy development. The Model Organism Development and Evaluation for Late‐onset AD (MODEL‐AD) Center is developing and distributing novel mouse models carrying human‐relevant risk factors. Characterization of aging mice that better phenocopy human disease will reveal more appropriate disease pathways useful in the treatment of LOAD. Method: Humanized amyloid‐beta (Aβ) in addition to APOEε4 and Trem2*R47H, two risk factors of LOAD, were incorporated into C57BL/6J mice to produce the triple homozygous LOAD2 model. Cohorts of mice were aged on multiple sites to 4‐, 12‐, 18‐, and 24‐month timepoints. In some mice, high‐fat diet replaced normal mouse chow. A phenotyping pipeline designed to qualify disease states was implemented to measure behavior, cognition, and wellness. In vivo imaging of brain perfusion and metabolism, is also included, as is post‐mortem analyses of blood chemistry, neuropathology, transcriptomics, metabolomics, proteomics, spatial profiling, and electrophysiology. Result: Expression of nonmutated Aβ did not yield in 18‐month mice. By 12 months, LOAD2 mice did not display penetrant behavioral phenotypes. High‐fat diet increased frailty scores in all cohorts irrespective of genotype. LOAD2 mice show increased plasma cytokines and neuroinflammation in 12‐month animals without overt hippocampal pathology. Long‐term potentiation is preserved in LOAD2 animals until 12‐months. Correlation of transcriptional profiling with human AMP‐AD modules determined individual and synergistic effects between genetic and environmental risk factors. Neuropathology and in vivo imaging analysis of brain tissue is in progress, as are cytokine panels in brain homogenates and plasma. Conclusion: The MODEL‐AD consortium has established the LOAD2 mouse model to study the effects of genetic and environmental risk factors of LOAD. This strain serves as a platform for the incorporation of additional AD risk factors (both genetic and environmental to more closely align phenotypes in the mouse to outcomes observed in the clinic. Ultimately, strains carrying combinations of AD risk factors that more closely align with human disease will be incorporated into the pre‐clinical testing core of MODEL‐AD to assess the potential of prioritized therapeutic compounds.